2010
DOI: 10.1086/656363
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz versus Boosted Atazanavir or Zidovudine and Abacavir in Antiretroviral Treatment–Naive, HIV‐Infected Subjects: Week 48 Data from the Altair Study

Abstract: A novel quadruple nucleo(t)side combination demonstrated significantly less suppression of HIV replication, compared with the suppression demonstrated by standard antiretroviral therapy regimens, although it did meet the predetermined formal definition of noninferiority. Secondary analyses indicated statistically inferior virologic and safety performance. Efavirenz and ritonavir-boosted atazanavir arms were equivalent in viral suppression and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 32 publications
0
57
0
Order By: Relevance
“…18 Conversely, other randomized controlled studies such as the ACTG A5202 study or the Altair study have demonstrated equivalent efficacy with efavirenz-versus boosted atazanavir-based regimens. 19,20 However, these studies excluded patients with known baseline NNRTI resistance and thus cannot specifically address the issue. A subanalysis of A5202 comparing the efficacy of efavirenz and boosted atazanavir between different males and females showed the inferiority of boosted atazanavir in in black race and females.…”
mentioning
confidence: 99%
“…18 Conversely, other randomized controlled studies such as the ACTG A5202 study or the Altair study have demonstrated equivalent efficacy with efavirenz-versus boosted atazanavir-based regimens. 19,20 However, these studies excluded patients with known baseline NNRTI resistance and thus cannot specifically address the issue. A subanalysis of A5202 comparing the efficacy of efavirenz and boosted atazanavir between different males and females showed the inferiority of boosted atazanavir in in black race and females.…”
mentioning
confidence: 99%
“…Consistent with the trend towards earlier initiation of ART, the median baseline CD4 cell count at which patients start ART has risen in the past decade in all regions; however, the proportion of people initiating ART with very low CD4 counts remains high, with more than one in four patients starting ART at CD4 count 100 cells per μL or less across all regions. 32 Patients presenting with a low CD4 cell count are at increased risk of death in both low and high-income settings, 33,34 and determination of CD4 count has an important role in decisions for screening and prophylaxis for major opportunistic infections. A low CD4 count is predictive of several diseases associated with increased mortality, including cryptococcal meningitis, pneumocystis pneumonia, toxoplasmosis, Mycobacterium avium complex, and disseminated cytomegalovirus disease.…”
Section: 28mentioning
confidence: 99%
“…The fixed-dose combination Atripla and the individual components have been evaluated in a number of clinical trials in comparison to alternate agents including NNRTI (nevirapine, etravirine [ETR], rilpivirine [RPV]), ritonovir-boosted protease inhibitor (PI-r) (lopinavir-ritonavir [LPV-r], atazanavir-ritonavir [ATZ-r]) integrase inhibitors (raltegravir [RAL], elvitegravir), and CCR-5 inhibitors (maraviroc). [25][26][27][28][29][30][31][32][33][34][35] In the studies to date, largely of noninferiority design, and using the primary endpoints as defined by the studies, Atripla has not been beaten for efficacy by any other agent.…”
Section: Efficacymentioning
confidence: 99%
“…29 When comparing groups in a higher virologic strata (HIV-1 viral load $ 100,000 copies/mL), patients taking ABC-3TC combined with boosted-ATZ had higher rates of virologic failure than those taking ABC-3TC combined with EFV (HR, 1.68; 95% CI: 1.08 to 2.60; P = 0.019). 37 The Altair study found that a quadruple NRTI regimen (TDF-FTC-ZDV-ABC) was inferior to TDF-FTC-EFV, mostly due to therapy discontinuations from adverse events in the ITT analysis, although there was no difference of the latter to TDF-FTC-ATZ-r. 30 The STARTMRK study was the first study comparing TDF-FTC-EFV to an integrase inhibitor-based regimen. 566 treatment-naïve patients were randomized to Truvada (TDF-FTC) plus either EFV or RAL.…”
Section: Efficacymentioning
confidence: 99%